Mechanistic role of pyroptosis in tumor microenvironment and tumor immunotherapy: Role of pyroptosis in cancer inhibition - Attar, Rukset; Qureshi, Muhammad Zahid; Sabitaliyevich, Uteuliyev Yerzhan; Yulaevna, Ishmuratova Margarita; Romero, Mirna Azalea (Cellular and Molecular Biology, 2024)
In recent decades, extraordinary attention has been devoted to cell death pathways principally because of multifaceted regulatory roles in normal developmental and pathophysiological processes. The removal of functionally defective, infected or potentially malignant cells is regulated by programmed cell death (PCD) cascades. Pyroptotic cell death is a highly complicated pro-inflammatory form of cell death. Pyroptosis is characterized by the formation of pores in the plasma membrane by oligomerization of the N-terminal fragment of gasdermins (gasdermin-NT) following the cleavage of gasdermin. Pyroptosis plays a pivotal role in the innate immune responses and mechanistically steered by inflammasome-mediated and inflammasome-independent cascades. In this review, we have comprehensively analyzed how different signaling pathways regulated pyroptosis in cancer inhibition and metastatic spread of cancer cells to the secondary sites. Comprehensive understanding of the interconnection between signaling pathways and pyroptosis will enable us to reap maximum benefits from the exciting mechanistic insights gained from pioneering studies related to pyroptosis.